Pengaruh Strategi Pembelian Terhadap Performa Perusahaan di Jabodetabek Dengan Integrasi Pembelian Sebagai Variabel Moderasi - Evelyn Nathalia; Riris Loisa (Universitas Tarumanagara, 2020)
This study was conducted to analyze the effect of purchasing strategies, namely negotiations, relationships with suppliers, cost management, and supply management on company performance in Jabodetabek which is moderated by purchasing integration. This research was obtained from primary data in the form of questionnaire results that were distributed for five months (February 2019-June 2019). This questionnaire was filled in by respondents who worked as procurement in a company located in Greater Jakarta. Respondents will fill out a questionnaire using a Likert scale with a scale of 1-6, namely